Effects of acute caffeine ingestion on repeated sprint ability: A systematic review and meta-analysis - Wang, Y.; Su, W.; Zhang, S.; Zhao, L.; Lv, Y.; Gu, B.; Yu, L. (Nutrients, 2025)
Background/Objectives: Caffeine is widely recognized as an ergogenic aid, yet evidence regarding its acute effects on repeated sprint ability (RSA) remains inconsistent. This systematic review and meta-analysis aimed to evaluate the effects of acute caffeine ingestion on RSA across different populations, exercise modalities, and dosage levels.